2019
DOI: 10.18502/ijpa.v14i1.733
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Description of Sarcocystis Sp. in Cardiac Muscle of Naturally Infected Alpacas (Vicugna pacos)

Abstract: Background: Recently, it was proposed the name of Sarcocystis masoni n. sp. for the Sarcocystis that causes microcyst in skeletal muscle of South American camelids. However, there are no ultrastructural reports of microcysts of Sarcocystis in cardiac muscle of alpacas. This study reports ultrastructural features of microcysts of Sarcocystis sp. from cardiac muscle of naturally infected alpacas. Methods: Thirty alpacas (age range: three to five years) from the province of Junin, Peruvian Central Andes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other authors also found 100% prevalence rates of myocardium of alpacas infected with S. masoni n. sp. "lamacanis" (Guerrero et al, 1967;López-Torres et al, 2015;Lucas et al, 2019a). No in ammatory reaction against the microcysts was observed (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other authors also found 100% prevalence rates of myocardium of alpacas infected with S. masoni n. sp. "lamacanis" (Guerrero et al, 1967;López-Torres et al, 2015;Lucas et al, 2019a). No in ammatory reaction against the microcysts was observed (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 97%
“…S. masoni n. sp. produces microcysts in cardiac tissue (Lucas et al, 2019a) and skeletal muscle (Moré et al, 2016). The de nitive host of this parasite is still unknown (Moré et al, 2016), although some studies have suggested that canids also play this role (Leguía et Histology is frequently used to diagnose Sarcocystis in muscle tissues (Bucca et al, 2011;Kojouri et al, 2011;López-Torres et al, 2015) as it could provide information such as the level of adaptation of the parasite to its host.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of 43 sera from S. aucheniae-positive llamas against p niae cysts was determined in immunoblots (Figure 1). All positive ser or more protein bands of 23,26,33,38,45, and 73 kDa, which were rec 63, 53, 14, and 23% of the tested S. aucheniae-positive sera, respectivel bands were recognized by sera of S. aucheniae-negative llamas (data no 114 phase separation showed that the detected immunoreactive prot partitioned into the soluble fraction (Figure 1).…”
Section: Llama Anti-s Aucheniae Igg Antibodies Recognize Six Immunore...mentioning
confidence: 96%
“…The reactivity of 43 sera from S. aucheniae-positive llamas against proteins of S. aucheniae cysts was determined in immunoblots (Figure 1). All positive sera reacted with one or more protein bands of 23,26,33,38,45, and 73 kDa, which were recognized by 21, 15, 63, 53, 14, and 23% of the tested S. aucheniae-positive sera, respectively. No cyst protein bands were recognized by sera of S. aucheniae-negative llamas (data not shown).…”
Section: Llama Anti-s Aucheniae Igg Antibodies Recognize Six Immunore...mentioning
confidence: 98%
“…Microscopic sarcocysts, referred to as Sarcocystis sp., S. lamacanis or, more recently, S. masoni , were reported in the cardiac muscle of llamas and guanacos from Argentina, alpacas from Peru, and alpacas bred in the extra-Andean countries China, Iran, and Australia [ 17 , 33 , 46 , 62 , 63 , 64 , 65 , 66 ]. Microcysts were, in some cases, also observed in other body locations in addition to the myocardium, such as liver, kidney, spleen, lung, tongue, and skeletal muscles [ 17 , 33 , 62 , 63 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%